2015
DOI: 10.1186/s12882-015-0103-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphatemia as an independent risk factor for coronary artery calcification progression in peritoneal dialysis patients

Abstract: BackgroundCoronary artery calcification (CAC) is associated with cardiovascular mortality in end-stage renal disease (ESRD) patients. The present study aimed to identify modifiable risk factors for CAC progression in peritoneal dialysis (PD) patients.MethodsAdult patients who received regular PD for more than 6 months and underwent a series of coronary artery calcification score (CaCS) measurements by multislice spiral computed tomography (MSCT) with an interval of ≥ 6 months were included in this observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…In previous studies, the phosphate was proved to be associated with CAC progression and the mortality in both general and CKD patients [14, 2831]. In our study, the hyperphosphatemia was related to the CAC initiation in PD patients.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In previous studies, the phosphate was proved to be associated with CAC progression and the mortality in both general and CKD patients [14, 2831]. In our study, the hyperphosphatemia was related to the CAC initiation in PD patients.…”
Section: Discussionsupporting
confidence: 64%
“…The CaCS was recorded as just as we previous described [6, 14]. Demographic characteristics and comorbidities (diabetes mellitus, hypertension, and CVD) were recorded at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, higher serum phosphate concentrations falling within the normal range are associated with cardiovascular events and mortality in patients with normal and abnormal kidney function (9,87). A recent study by Shang et al (88) showed that hyperphosphatemia is an independent risk factor in the progression of coronary artery calcification. Phosphate levels were positively associated with protein intake and peritoneal dialysis adequacy, suggesting that restriction of phosphate intake may be useful in slowing the progression of vascular calcification.…”
Section: Phosphate and Cardiovascular Diseasementioning
confidence: 99%
“…12,13 According to Shang's study, hyperphosphatemia is an independent risk factor for coronary artery calcification progression. 27 Vascular calcification is an early feature of CKD patients and its progression is linked to high phosphate load and hyperphosphatemia. Therefore, Lioufas suggests a reduction of the level of phosphatemia in chronic renal failure to reduce the risk of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%